2008
DOI: 10.1002/erv.849
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes, prejudice and discrimination of women with anorexia nervosa

Abstract: Limited research indicates that public attitudes toward individuals with eating disorders are moderately negative. The present study examined specific forms of stigmatisation attributed to individuals with anorexia nervosa (AN). Eighty female participants recruited from an undergraduate institution completed questionnaires assessing stereotypes, prejudice and discrimination of four target individuals: a woman with AN, depression, schizophrenia and mononucleosis. AN was considered to result more from lack of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 27 publications
6
44
0
Order By: Relevance
“…Previous research investigating the lay beliefs and stigma associated with EDs has tended to recruit adult community or university samples rather than adolescents, Help-seeking is also likely to be undermined by the negative attitudes to people with EDs that this research revealed. The results confirm previous international findings that among the general population, EDs are stigmatised to a greater extent than other mental or physical health conditions (Roehrig & McLean, 2010;Stewart et al, 2006Stewart et al, , 2008Crisp, 2005;Griffiths et al, 2014b). The differential responses to the various vignettes show that unfavourable attitudes were present in this adolescent sample.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous research investigating the lay beliefs and stigma associated with EDs has tended to recruit adult community or university samples rather than adolescents, Help-seeking is also likely to be undermined by the negative attitudes to people with EDs that this research revealed. The results confirm previous international findings that among the general population, EDs are stigmatised to a greater extent than other mental or physical health conditions (Roehrig & McLean, 2010;Stewart et al, 2006Stewart et al, , 2008Crisp, 2005;Griffiths et al, 2014b). The differential responses to the various vignettes show that unfavourable attitudes were present in this adolescent sample.…”
Section: Discussionsupporting
confidence: 91%
“…The differential responses to the various vignettes show that unfavourable attitudes were present in this adolescent sample. Specifically, and consistent with previous research in other jurisdictions (Roehrig & McLean, 2010;Stewart et al, 2006Stewart et al, , 2008Crisp, 2005), young people tended to hold individuals with EDs personally responsible for their illness and ascribe more negative characteristics to them compared to those with depression and T1 diabetes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Research shows that the social stigma surrounding ED is a major barrier to seeking help (Booth et al 2004;Hackler et al 2010;Griffiths et al in press). Studies conducted in the United States and the United Kingdom suggest that people with EDs are viewed negatively by the public (Crisp, 2005;Stewart et al 2008). Specifically, compared with other mental and physical illnesses, EDs are more often seen as self-inflicted or reflecting attention-seeking (Crisp, 2005;Stewart et al 2006;Crisafulli et al 2008;Roehrig & McLean, 2010;Ebneter & Latner, 2013;McLean et al 2014).…”
Section: Healthcare Professionals' Attitudes Towards Edsmentioning
confidence: 99%
“…Specifically, compared with other mental and physical illnesses, EDs are more often seen as self-inflicted or reflecting attention-seeking (Crisp, 2005;Stewart et al 2006;Crisafulli et al 2008;Roehrig & McLean, 2010;Ebneter & Latner, 2013;McLean et al 2014). These negative projections may result in dissociation from individuals with EDs (Crisp, 2005;Stewart et al 2008;Zwickert & Rieger, 2013), which can foster a sense of isolation among those affected and a reluctance to disclose their illness.…”
Section: Healthcare Professionals' Attitudes Towards Edsmentioning
confidence: 99%